Purification and characterization of bacteriocins from lactic acid bacteria / Wayah Samson Baranzan - Wayah Samson, Baranzan (2019)

(untitled)
Staphylococcus aureus, Streptococcus mutans, Micrococcus luteus, Listeria monocytogenes and Bacillus cereus are major threats to human life. For many years antibiotics have been the weapon of choice against these pathogens and food spoilage bacteria. However, in recent times, antibiotic resistance has emerged making these antibiotics ineffective. More so, consumer’s inclination towards food containing less chemical preservatives continues to rise. The need for alternative antimicrobials is important to combat harmful microorganisms and minimize the adverse effects of antibiotic overuse. A study was therefore undertaken to isolate, purify and characterize novel bacteriocins produced by lactic acid bacteria (LAB). In this study, three (3) novel bacteriocins highly potent against Staphylococcus aureus, Streptococcus mutans, Micrococcus luteus, Listeria monocytogenes and Bacillus cereus were isolated, purified and characterized. LAB strains were isolated and screened for production of highly potent bacteriocins. These bacteriocins were purified to homogeneity and characterized. Optimization and scale-up of bacteriocin production was carried out. Biochemical characterization, antibiotic susceptibility and hemolysis test of the bacteriocin producers was conducted. Mechanism of action and regulation of biosynthesis was investigated. Biopreservative potential of these bacteriocins was assessed in vivo. Pentocin MQ1, a novel bacteriocin produced by Lactobacillus pentosus CS2 was isolated and purified. MALDI-TOF mass spectrometry revealed that the molecular weight was 2.11 kDa. This bacteriocin possessed heat and chemical stability, bactericidal and highly potent against selected food spoilage and pathogenic bacteria. It acted against its targets via membrane permeabilization. Pentocin MQ1 is cell-wall associated and its biosynthesis auto-inducible. A newly synthesized medium was found to be more suitable for its production than the current commercially available media. Salivaricin mmaye1 was isolated from iv Lactobacillus salivarius SPW1 of human gut origin. It has a molecular weight of 1.22 kDa as determined by MALDI-TOF mass spectrometry. It has a broad spectrum of antibacterial activity. Media type and initial pH of broth influenced bacteriocin production. Salivaricin mmaye1 production is regulated by a quorum sensing mechanism. Salivaricin mmaye1 is cell-wall associated and possessed a bactericidal mode of action against its targets. It is quick-acting and its action is mediated by pore formation. Scale-up optimization of bacteriocin production was achieved. Lactobacillus fermentum GA715 of goat milk origin produces a novel, cell-wall associated, non-pore forming bacteriocin called fermencin SA715. Its molecular weight is 1.79 kDa as determined by MALDI-TOF mass spectrometry. Bacteriocin production could not occur in the absence of manganese (II) sulphate in the growth medium. Tween 80, ascorbic acid, sodium citrate and magnesium sulphate enhanced the production of fermencin SA715. Sucrose is the preferred carbon source for this medium. Sodium chloride concentration greater than 1 % suppressed growth and production of fermencin SA715. Optimum bacteriocin production occurred at 37 0C and at pH 6-7. Scale up of production in a fermenter at a constant pH proved successful. Fermencin SA715 possesses high thermal and pH stability. Pentocin MQ1, salivaricin mmaye1 and fermencin SA715 were found to increase the microbiological quality and shelf-life of banana in vivo. Lactobacillus pentosus CS2, Lactobacillus salivarius SPW1 and Lactobacillus fermentum GA715 are non-hemolytic and susceptible to most antibiotics tested. In conclusion, this study reveals the huge potential of pentocin MQ1, salivaricin mmaye1, fermencin SA715 and their producers paving the way for future applications ex situ or in situ in biopreservation of food and novel probiotic applications.